Dissolution factors and oxidative potential of acid soluble irons from chlorite mineral particles. (15th June 2021) - Xie, Tingting; Lu, Senlin; Rao, Lanfang; Zhang, Luying; Wang, Xingzi; Wang, Weiqian; Wang, Qingyue
Abstract: Soluble irons from aerosol particles play a key role in assessment of biological and toxicological effects as a result of their oxidative potential. Several factors are responsible for controlling the solubility of irons released from aerosol mineral particles in acid solution. Here, factors of H + concentrations, temperatures, solid–liquid ratios and particle sizes on acidsoluble irons from chlorite mineral particles were investigated in 48h. Our data demonstrated that the higher acidity, higher temperature, lower solid–liquid ratio, and smaller particle size were factors that positively influenced the solubility of FeT and Fe(II), and that the higher acidity, lower temperature, higher solid–liquid ratio, and smaller particle size positively improved the solubility of Fe(III). Fe(II) dissolved more easily than Fe(III) in the acid solution under all conditions; the percentage of Fe(III) among the total iron released from chlorite particles could be promoted by increasing the acidity, solid–liquid ratio, and particle size, or by lowering the temperature. In this acidolysis process, there is a clear order of importance of these influencing factors, H + concentrations > particle sizes > temperatures and solid–liquid ratios. In addition, the dissolution data for FeT at pH = 0.7 and pH = 1 in 48 h could be well described and predicted by non-linear fitting with r 2  > 0.99 according to continuous dissolution model. And the analysis of oxidative potential showed that Fe(II) dissolved from chlorite possessed a dominant position in generating reactive oxygen species. Graphical abstract: Image 1 Highlights: Acidity, temperature, solid-liquid ratio and particle size positively affected the solubility of FeT and Fe(II). Fe(II) dissolved more easily than Fe(III) in acid solution. Fe(II) displayed a dominant position in generating reactive oxygen species.